(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
Female undergarments and shapewear has been of relevance to the culture and lifestyle of various generations in the past evolving from the use of metal corsets, whale bones, control-top pantyhose, and now the panty girdle. Shapewear has been a pivotal feature of the female outlook and fashion; thus forming an essential part of the everyday apparel of today’s woman. Over the years shapewear has taken very different forms, some close to what could be described as torcher (causing physical pain and ill-health in women), with others being comfier as it fulfills its purpose of projecting the desired feminine stature. As such, this study was developed to examine the effect and comfortability of modern shapewear, particularly Panty girdles. A questionnaire was developed and delivered to a sample of 500 nurses in the city of Accra -Ghana (West Africa) to solicit data on the use of panty girdles. The findings of the study revealed that panty girdles were generally comfortable and presented no significant interruptions to work performance for Ghanaian nurses. Further, the study showed that panty girdles were effective in shaping the body of their users. However, the data reveals that there is a significant association between the type of panty girdle used and the levels of comfort experienced users. In the future, the four selected panty girdles will be experimented to show the scientific methods and to help back this survey.